Subventricular zone neural precursor cell responses after traumatic brain injury and binge alcohol in male rats. Issue 5 (7th January 2019) - Ton, Son T.; Tsai, Shih‐Yen; Vaagenes, Ian C.; Glavin, Kelly; Wu, Joanna; Hsu, Jonathan; Flink, Hannah M.; Nockels, Daniel; O'Brien, Timothy E.; Kartje, Gwendolyn L.
Abstract: Traumatic brain injury (TBI) is a major cause of disability worldwide. Additionally, many TBI patients are intoxicated with alcohol at the time of injury, but the impact of acute intoxication on recovery from brain injury is not well understood. We have previously found that binge alcohol prior to TBI impairs spontaneous functional sensorimotor recovery. However, whether alcohol administration in this setting affects reactive neurogenesis after TBI is not known. This study, therefore, sought to determine the short‐ and long‐term effects of pre‐TBI binge alcohol on neural precursor cell responses in the subventricular zone (SVZ) following brain injury in male rats. We found that TBI alone significantly increased proliferation in the SVZ as early as 24 hr after injury. Surprisingly, binge alcohol alone also significantly increased proliferation in the SVZ after 24 hr. However, a combined binge alcohol and TBI regimen resulted in decreased TBI‐induced proliferation in the SVZ at 24 hr and 1 week post‐TBI. Furthermore, at 6 weeks after TBI, binge alcohol administered at the time of TBI significantly decreased the TBI‐induced neuroblast response in the SVZ and the rostral migratory stream (RMS). The results from this study suggest that pre‐TBI binge alcohol negatively impacts reparative processes in the brain by decreasing short‐term neural precursor cell proliferative responses as well as long‐term neuroblasts in the SVZ and RMS. Abstract : A combined binge alcohol and traumatic brain injury (TBI) regimen decreased proliferation in the subventricular zone (SVZ) at 24 hr and 1 week post‐TBI. At 6 weeks post‐TBI, binge alcohol administered at the time of TBI decreased the neuroblast response from the SVZ.